The Effectiveness of Spatial Agrarian Functions/National Land Agency in Resolving Land Disputes Through Mediation - Jihan Fahirah S. Rahman H. Baharuddin (Gerechtiheid Law Journal, 2021)
The aims of this study are (i) to analyze and explain the effectiveness of the ATR/BPN function in resolving land disputes in Maros Regency, and (ii) to analyze and explain the factors that influence the effectiveness of the ATR/BPN function in resolving disputes through mediation. This research is an empirical research, namely legal research conducted with an approach to the legal reality in society. The data analysis technique used is descriptive qualitative, that is, after the data has been collected it is then poured in the form of a logical and systematic description, then analyzed to obtain clarity of problem solving, then deductive conclusions are drawn, namely from general things to specific things. The results of this study indicate that as a mediator, the ATR/BPN Office of Maros Regency has the function of assisting the parties in understanding each other's views and helping to find things that are considered important to them. Mediation within the land agency environment, in this case the ATR/BPN Office of Maros Regency, actually makes it easier for the community to resolve land disputes because at this time mediation efforts already have a legal umbrella equipped with adequate technical guidelines and instructions so that there is no doubt for the implementing apparatus to carry it out.